Peran Orangtua Terhadap Pencegahan Kasus Kekerasan Seksual pada Anak Usia Dini - NASUTION, RISKHA HANIFA; Frasandy, Rendy Nugraha (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The large number of cases of sexual violence that occur against children require special attention, especially from parents. The role of parents is to provide children with knowledge from an early age regarding sexual violence in accordance with their development. This article serves as a guide and increases knowledge for readers about the importance of the role of parents in preventing cases of sexual violence in early childhood. With the literature review method using sources from various research results that have been carried out. Establishing effective communication between children and parents is one way for parents to provide knowledge to prevent sexual violence against children. Parents are the figures closest to children so that children have more freedom and ease to ask questions or tell stories.